They came to play [videorecording (DVD)] - Rotaru, Alex (Docurama Films : Distributed by New Video, 2010)
Focuses on the International Piano Competition for Outstanding Amateurs, which gathers together 75 of the world's best amateur pianists for one week of intense competition and camaraderie. Candid interviews offer a glimpse into the lives of the competitors, who come from a wide variety of backgrounds and professions.